Формування екологічної культури в учнів початкової школи - Біда Олена; Орос Ільдіко; Гончарук Віталій; Bida Olena; Orosz Ildikó; Goncharuk Vitaliy; Oros Ildiko (РВВ ЦДПУ ім. В. Винниченка, 2020)
Резюме. У статті розкрито основи формування екологічної культури в учнів початкової школи. Вчені все частіше говорять не просто про навчання молодого покоління, а про екологічну освіту як індивідуальний процес розвитку особистості. Культура є комплексом суб’єктивацій і об’єктивацій, які обов’язково мають засвоюватися в процесі кроскультурної освіти та використовуються в повсякденній орієнтації. Найважливіша функція культури – це те, що вона є способом, за допомогою якого суспільства вирішують проблеми.

Abstract. The basics of formation of ecological culture in elementary school students are revealed. Increasingly, scientists are talking not just about teaching the younger generation, but about environmental education as an individual process of personal development. Culture is a complex of subjectivities and objectifications that must be learned in the process of crosscultural education and are used in everyday orientation. The most important function of culture is that it is the way in which societies solve problems. Culture has four basic elements: concepts (concepts), relationships, values, rules and norms. Each of these components plays an extremely important role in creating students' cultural image and environmental education. The most important function of culture is that it is the way in which society solves problems. Given the current global trends, the formation of elementary school students of ecological culture is of particular importance in Ukraine. State programs, state documents aimed at promoting healthy lifestyles of children and youth are outlined. One of the main tasks of education is to educate conscious attitudes towards one's own health and the health of others, to form hygienic skills and principles of healthy lifestyles, to preserve and strengthen them. health of the younger generation. Scientists are talking not just about teaching the younger generation, but about environmental education as an individual process of personal development. Culture has four main elements: concepts (concepts), relationships, values, rules and norms. Each of these components plays an extremely important role in creating students' cultural image and environmental education. The most important function of culture is that it is the way in which society solves problems. Given the current global trends, the formation of elementary school students of ecological culture is of particular importance in Ukraine.
Formation of environmental culture in primary school pupils
https://pednauk.cuspu.edu.ua/index.php/pednauk/article/view/516
Keywords: культура; екологічна культура; учні; початкова школа; основні елементи культури